1993
DOI: 10.1007/bf00920237
|View full text |Cite
|
Sign up to set email alerts
|

P-glycoprotein (MDR 1 gene product) in cells of the immune system: Its possible physiologic role and alteration in aging and human immunodeficiency virus-1 (HIV-1) infection

Abstract: P-glycoprotein, a 170-kd glycoprotein encoded by the MDR 1 gene, is a member of a highly conserved superfamily of ATP-binding cassette (ABC) transport proteins. It shares extensive homology with numerous bacterial and eukaryotic ABC transport proteins. P-glycoprotein acts as an energy-dependent efflux pump that appears to transport structurally diverse agents ranging from ions to peptides. P-glycoprotein (P-gP) has been implicated as playing a role in multidrug (MDR) resistance in cancer, chloroquine-resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 52 publications
2
38
0
Order By: Relevance
“…However, the expression and function of surface P-gp by the majority of CD14 ϩ cells is different from several previous reports illustrating low P-gp expression on monocytes (10,11,14). Our findings, however, are consistent with one report that used another P-gp-specific mAb (MRK16) (31). Moreover, our finding of functional inhibition of calcein-AM dye efflux from purified CD4 ϩ T cells and monocytes by specific (Hyb-241 mAb) and pharmacologic P-gp inhibitors, a well-described function of P-gp in other cell types (30,32), confirmed that P-gp is functional in CD4 ϩ T cells and monocytes.…”
Section: Discussionsupporting
confidence: 93%
“…However, the expression and function of surface P-gp by the majority of CD14 ϩ cells is different from several previous reports illustrating low P-gp expression on monocytes (10,11,14). Our findings, however, are consistent with one report that used another P-gp-specific mAb (MRK16) (31). Moreover, our finding of functional inhibition of calcein-AM dye efflux from purified CD4 ϩ T cells and monocytes by specific (Hyb-241 mAb) and pharmacologic P-gp inhibitors, a well-described function of P-gp in other cell types (30,32), confirmed that P-gp is functional in CD4 ϩ T cells and monocytes.…”
Section: Discussionsupporting
confidence: 93%
“…The level of intracellular Rh 123 accumulation can be measured by flow cytometry. P-gp is expressed at high levels in tissues like the gastrointestinal tract, liver, and kidney and on capillary endothelial cells of the brain and on PBMCs (17, 26, 44,53,61,94,128,129). P-gp was found on freshly isolated CD4 ϩ and CD8 ϩ T cells.…”
Section: Tissue Distribution Of P-gpmentioning
confidence: 99%
“…P-gp expressed in the placenta plays an important role in the protection of the developing fetus against toxic substances (81,120). P-gp expression on bone marrow stem cells might protect them from toxic substances and could also be responsible for the transport of certain growth factors and cytokines produced by stem cells (53). It is unclear whether P-gp also has this function in other cell types.…”
Section: P-gp Functionmentioning
confidence: 99%
“…This function is illustrated elegantly in mice that lack one [Mdr1a (Ϫ͞Ϫ) or Mdr1b(Ϫ͞Ϫ)] or both drug-transporting P-gps, because these mice have profound defects in drug distribution (5,14,15). High P-gp expression also is found in hematopoietic pluripotent stem cells and specific lymphocyte lineages, including NK cells and mature single positive thymocytes (16)(17)(18). Significantly, P-gp is expressed in developing organs of the early fetus where the ordered process of cell differentiation and death is necessary for correct organogenesis.…”
mentioning
confidence: 99%